PEMBUATAN BIOPORI PADA LAHAN KOPI DALAM UPAYA MENINGKATKAN PRODUKTIVITAS KOPI - Syarifuddin; Khairul Anshar; Bakhtiar; Rizka Mulyawan; Agam Muarif (Politeknik Negeri Sriwijaya, 2022)
Abstract Arabica coffee is one type of coffee that dominates most of the world's coffee market. In Indonesia, arabica coffee can be found in Bali, Java, North Sumatra, Toraja and the Gayo Highlands. The Gayo Highlands are the best coffee producers in Indonesia. One of the determinants of coffee quality and productivity is the quality of coffee plantations. The problems faced by coffee farmers in Pante Raya Village, Kab. Bener Meriah is a dense soil condition because the land was previously used as paddy fields. As for the coffee plantation area of 1 ha, the yield of coffee beans is 2 tons with coffee husk waste as much as 1 ton per year. For now, the coffee skin is just trash. On the other hand, people use fertilizers to maintain and increase coffee productivity, but it costs a lot. Seeing these problems, community service was carried out in Pante Raya Village, Bener Meriah Regency by making biopori using coffee husk waste, leaves and twigs of coffee plants. The installation of this biopore is expected to be useful as a waste treatment medium that is useful for fertilizing the soil, increasing soil pores and absorption of water in the soil. This service activity will be carried out in the form of direct education and training on making biopori by utilizing the waste. Biopori is expected to reduce waste as well as provide alternative fertilizers that are safe and cheap. Keywords: Coffee, Gayo, biopori, waste, fertilizer